Microfluidics Synthesis of Gene Silencing Cubosomes - Kim, Hojun; Sung, Jaeuk; Chang, Yunju; Alfeche, Alana; Leal, Cecilia (AMER CHEMICAL SOC, 2018)
The success of gene technologies hinges on our ability to engineer superior encapsulation and delivery vectors. Cubosomes are lipid-based nanoparticles where membranes, instead of enveloping into classic liposomes, intertwine into complex arrays of pores well-ordered in a cubic lattice. These complex nanoparticles encapsulate large contents of siRNA compared to a liposomal analogue. Importantly, the membranes that form cubosomes have intrinsic fusogenic properties that promote fast endosomal escape. Despite the great potential, traditional routes of forming cubosomes lead to particle sizes too large to fulfill the state-of-the art requirements of delivery vectors. To overcome this challenge, we utilize a microfluidic nano-manufacturing device to synthesize cubosomes and siRNA-loaded cubosomes, termed cuboplexes. Utilizing cryogenic TEM and small angle X-ray scattering we elucidate the time-resolved mechanisms in which microfluidic devices allow the production of small cubosomes and cuboplexes (75 nm) that outperform commercially available delivery vectors, as well as liposome-based systems.